2015
DOI: 10.1039/c5cp03927d
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-electronic properties of graphene nanoribbons with various edge structures passivated by phosphorus and hydrogen atoms

Abstract: The electronic and magnetic structures of graphene nanoribbons (GNRs) with various edge structures passivated by P atoms are investigated systematically, and compared with H passivation as well. GNRs with the entire reconstructed Klein edge or armchair edge are found to be nonmagnetic regardless of P or H passivation. However, if the edge of GNRs is a mixture of zigzag edge and reconstructed Klein edge, they are nonmagnetic for H passivation but significantly magnetic for P passivation, which could be attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…However, for the remainder of the studied materials, with non-negligible spin polarisation, a sizeable band gap opens at the Dirac point, ranging from 1 eV (GY) to 2 eV (GDP). In line with these results, the correlation between radical centres with an AFM alignment of localised spins and the appearance of sizeable band gaps has been previously reported for nanoribbons of graphene 21 , 22 , 51 and GY 30 , 31 , as well as for isotropically strained graphene 27 . In all cases the gap opening can be rationalised by the breaking of the hexagonal symmetry of the system.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…However, for the remainder of the studied materials, with non-negligible spin polarisation, a sizeable band gap opens at the Dirac point, ranging from 1 eV (GY) to 2 eV (GDP). In line with these results, the correlation between radical centres with an AFM alignment of localised spins and the appearance of sizeable band gaps has been previously reported for nanoribbons of graphene 21 , 22 , 51 and GY 30 , 31 , as well as for isotropically strained graphene 27 . In all cases the gap opening can be rationalised by the breaking of the hexagonal symmetry of the system.…”
Section: Resultssupporting
confidence: 86%
“…1b have been reported to have intrinsic localised multi-radical and quinoidal electronic states. However, for graphene, experimental and theoretical studies have shown that such localised states can be generated by: (i) nano-patterning 18 20 , (ii) cutting it into nanoribbons 18 , 21 , 22 , (iii) covalent grafting of molecules 23 or atoms 24 , 25 , (iv) inclusion of defects 26 , or (v) applying external strains 27 , 28 . Analogously, computational modelling has predicted similar states in α-graphyne (GY) upon application of strain 29 or by forming α-GY nanoribbons 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…To further tune or improve magnetic features of graphene nanoribbons, other commonly-used manners include defect engineering [9][10][11], heteroatom doping [12], edge modifications [13][14][15][16] and surface adsorptions [17]. However, the defectintroduced nanostructures usually lack geometrical stability.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] It is well known that the ground state of ZGNRs is characterized by spin-polarized electronic states at two edges, which couple through the graphene backbone and result in an antiferromagnetic (AF) arrangement of spins on adjacent atomic sites with zero total magnetic moment. [7][8][9][10][11] In this regard, many works reported the electronic properties and chemical properties of the edge states of ZGNRs while the structure is modied by defects, [12][13][14][15] doping foreign atoms, [16][17][18][19][20][21] hydrogenation, [22][23][24][25][26][27][28][29][30] oxidation, 31 adsorption of some gas molecules [32][33][34][35] and external electric eld. [36][37][38] However, it remains a challenge to produce ferrimagnetic ZGNRs with modication of the structures.…”
Section: Introductionmentioning
confidence: 99%